Effect of element content fluctuation on partial melting behavior of coal ash particles. (1st July 2020) - Zhou, Zhihao; Shen, Zhongjie; Liang, Qinfeng; Xu, Jianliang; Liu, Haifeng
Highlights: Molten and unmelted areas could be found in the residual ash particles. Element enrichment status differed in local molten and unmelted areas. Element content fluctuation was reduced at higher temperatures. Substances containing sodium and silica were related to the initial liquid slag formation. Abstract: This study investigates the partial melting behavior difference of ash particles at sub-particle scale, correlating to the element fluctuation, with the experiment in a high temperature stage microscope (HTSM). Scanning electron microscopy (SEM) coupled with energy dispersive spectrometry (EDS) was employed to clarify the different local melting behavior of residual ash particles. It was found that the element enrichment status differed in the local molten and unmelted areas existing in the residual ash particles. Sodium and silicon tended to be rich in the molten areas while the element content of Mg, Al, Ca, Fe and S was comparatively higher in the unmelted areas. As the combustion temperature approached the ash deformation temperature of the three coals, the difference in the major element content was reduced. Results calculated by FactSage software showed that the initial liquid phase formed at the temperatures lower than the ash deformation temperature of the three coal ash samples. Na-rich minerals such as nepheline and albite are closely related to the formation of the liquid phase with low melting temperature. Element fluctuation may lead to the composition of local areas locating in the areas with low liquidus temperature on the phase diagram. In addition, relatively large fluctuations in silicon content have a significant effect on the position in the phase diagram. Thus, the ash melting behavior differs at sub-particle scale.